IDENTIFIKASI KEANEKARAGAMAN JENIS SERANGGA YANG BERPOTENSI HAMA PADA TANAMAN JAGUNG (Zea mays L.) DI DESA BANGUN JAYA KECAMATAN TOMONI KABUPATEN LUWU TIMUR - Ferdian Rahmadan; Ridha Yulyani Wardi; Eva Sohriati (Cokroaminoto Journal of Biological Science, 2023)
This study aims to determine the types of insects that have the potential to be pests and to determine the index of diversity of insect species that have the potential to be pests in corn plants. This research was conducted from January 2023 to February 2023 which is located on a corn plantation in Bangun Jaya Village, Tomoni District, East Luwu Regency. In this study using a quantitative descriptive method. Based on the research that has been done, three orders were found, namely Lepidoptera, Coeleoptera, and Hemiptera and there were 5 families, namely Noctuidae, Coccinellidae, Pentatomidae, Alydidae and Chrysomelidae and 7 species of insect pests, namely Spodoptera frugiperda, Helicoverpa armigera hubner, Menochilus sexmaculatus, Epilachna admirabilis, Scotinophara coarctata, Leptocorisa oratorius Fabricius and Aspidomorpha miliaris. The diversity index of insect species that have the potential to be pests in corn plantations is 1.82 and is included in the medium category.